The Influence Of Service Quality On Community Satisfaction In The Development Of Population Administration: Case Study at Kependudukan and Pencatatan Sipil Offices of Surade Region, Sukabumi Regency - Suci Ayu Sudari; Yuni Pambreni; Rohmat Hidayat (Neo Journal of economy and social humanities, 2022)
The study aims to know the influence of service quality on community satisfaction in the development of population administration at Kependudukan and Pencatatan Sipil Offices of Surade Region, Sukabumi Regency. Along with developments, various public complaints are often found regarding the decline in professionalism in public services in almost all government sectors or regions which are marked by a decrease in the quality of public services, especially in making population administration according to procedures. The variables used in this study are service quality as an independent variable and community satisfaction as the dependent variable. This study used questionnaire as the instrument of collecting data. Analysis data for this study used simple regression analysis. The result showed that the hypothesis testing for the effect of service quality on satisfaction obtained a t-count value of 8.361 with a significance level of 0.000 <0.05 then and the t-count value = 8.361 > t-table = 1.661, so that the service quality variable has significant and positive effect on satisfaction.